The impact of mechanical log surface damage on fibre loss and chip quality when processing Eucalyptus pulpwood using a single-grip harvester - Van der Merwe, Jaco-Pierre (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScFor)--Stellenbosch University, 2014.